Casting Defects And Mechanical Properties of Al-Si Alloy with Bangkalan Local Clay as Sand Casting Binder - Syaifullah, Candi Galih; Saputra, Ayik; Ruhyatul, Shabrina; Murdanto, Putut (Journal of Mechanical Engineering Science and Technology (JMEST), 2018)
This research is aimed to know the defect of casting, tensile strength, and hardness of Al-Si alloy to the variation of binder. The research method used is descriptive quantitative research method. This because the data is expressed in the form of numbers. This research uses pre-experimental research design using one-shot case study model. Based on the results of the study, it was found that most pinhole defects were owned by specimens using 90% bentonite binder that is 59 defects. Whereas the pinhole defect which is at least owned by the specimens using bangkalan local clay binder 9% that is 31 defects. The most common open grain structure defect is owned by metal casting specimens using a 9% bentonite binder, which is 81 defects. Whereas the defect of open grain structure is at least owned by the specimen result of casting of metal clad with bangkalan local clay 3% which amounted to 40 defects. The result of the research using bangkalan local clay binder of 9% has higher tensile strength than other binder. This is because the characteristic of bangkalan local clay which has a high content of calcium (Ca) is 92,81%. The value of the tensile strength of the bangkalan local clay is 12,8712 (kg/mm2), whereas the bentonite which is said to be the ideal binder for the mold has a tensile strength of 10,1612 (kg/mm2). The highest hardness value is owned by Al-Si alloy casting specimen with  bend mixture variation of bangkalan local clay 9% that is 128,033 HV. While the lowest hardness value is owned by Al-Si alloy casting foundry with 9% bentonite binder 114,4 HV